Comparative Study: Differences in Students' Geometric Reasoning Viewed from Van Hiele's Levels of Geometric Thinking - Thiara Ayu Sheila; Rika Mulyati Mustika Sari; Rafiq Zulkarnaen; Iyan Rosita Dewi Nur (Universitas Suryakancana, 2026)
This study aims to determine the differences in students' geometric reasoning in terms of Van Hiele's thinking levels in spatial geometry. This study used an ex post facto method with a quantitative approach. The population of this study was ninth-grade female students at SMP Negeri 2 Majalaya, with a sample of 86 students selected using simple random sampling. Data were obtained through diagnostic tests, geometric reasoning tests, and unstructured interviews with several samples. This study uses several inferential statistical tests such as normality tests, homogeneity tests, and ANOVA. The results of this study indicate that there are significant differences between the geometric reasoning abilities of students at level 0 and level 1, as well as between level 0 and level 2. The number of students classified as level 0 (visualization) is 69.77%; level 1 (analysis) is 24.42%; and level 2 (informal deduction) is 5.81%. No students were classified as level 3 or 4.